1998
DOI: 10.1002/(sici)1097-0290(19980705)59:1<99::aid-bit13>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic models for the growth ofEscherichia coli with mixtures of sugars under carbon-limited conditions

Abstract: In natural environments, heterotrophic microorganisms encounter complex mixtures of carbon sources, each of which is present only at very low concentrations. Under such conditions no significant growth could be expected if cells utilized only one of the available carbon compounds as suggested by the principle of diauxic growth. Indeed, there is much evidence that microbial cells utilize many carbon sources simultaneously. In order to predict bacterial growth under such conditions we developed a model describin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 31 publications
(48 reference statements)
1
59
0
Order By: Relevance
“…Harder et al (1977) demonstrated that the strain with the highest specific growth rate at the actual concentration of the growth-limiting nutrient out-competed all others, while Lendenmann & Egli (1998) proposed that under carbonlimited conditions heterotrophic bacteria which are able to utilize a wide range of the carbon compounds can grow faster than those which exhibit a narrow substrate spectrum. Therefore, it can be expected that P. corrugata SB4 would out-compete the other strains in the consortium.…”
Section: Discussionmentioning
confidence: 99%
“…Harder et al (1977) demonstrated that the strain with the highest specific growth rate at the actual concentration of the growth-limiting nutrient out-competed all others, while Lendenmann & Egli (1998) proposed that under carbonlimited conditions heterotrophic bacteria which are able to utilize a wide range of the carbon compounds can grow faster than those which exhibit a narrow substrate spectrum. Therefore, it can be expected that P. corrugata SB4 would out-compete the other strains in the consortium.…”
Section: Discussionmentioning
confidence: 99%
“…, and growth efficiencies of around 10 to 20% (del Giorgio & Cole 1998, Carlson et al 1999, to growth in nutrient-replete systems such as a laboratory culture with millimolar substrate concentrations, growth efficiencies of up to 60%, and specific uptake rates of 50 d −1 (Bailey 1977, Lendenmann & Egli 1998). …”
Section: Model Formulationmentioning
confidence: 99%
“…Among the members of the bacterial consortium, P. putida C exhibited the highest growth rate on aniline/4CA mixtures and the ability to grow on both aniline and 4CA. Harder et al (1977) demonstrated that the strain with the highest specific growth rate at the actual concentration of the growth-limiting nutrient out-competed all others, while Lendenmann and Egli (1998) proposed that under carbon limited conditions heterotrophic bacteria which are able to utilize a wide range of the carbon compounds can grow faster than those which exhibit a narrow substrate spectrum. Therefore, it can be expected that P. putida C would out-compete the other strains in the consortium.…”
Section: Discussionmentioning
confidence: 99%